ISSUES OF RELIGIOUS BELIEFS AND MIGRATION IN THE SOUTHERN LANDS OF CENTRAL ASIA IN ANTIQUITY AND THE EARLY MIDDLE AGES (Academia Science Repository, 2023)
This article discusses the issues of religious beliefs and migration in the southern countries of Central Asia in Antiquity and the early Middle Ages, as well as the historical roots, foundations and factors of these processes. The issues of religious beliefs and migration in the southern countries of Central Asia in antiquity and the early Middle Ages, as well as the relevance and reasons for studying the contribution of these processes to the development of the civilization of Uzbekistan on a scientific basis are discussed.